The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1111/j.1365-2125.2010.03751.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency re‐admissions to hospital due to adverse drug reactions within 1 year of the index admission

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECTADRs in hospital patients are a significant burden, though how often ADRs cause re-admission to hospital has not been well documented in the literature. WHAT THIS STUDY ADDS• One fifth of patients re-admitted to hospital within 1 year of discharge from their index admission were re-admitted due to an adverse drug reaction. • Admission to a medical ward, elderly age and prescription of anti-platelet agents or diuretics were identified as risk factors for re-admission due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 23 publications
2
102
1
5
Order By: Relevance
“…L'étude de Zhang et al [8] avait analysé rétrospectivement les facteurs prédictifs de réhospitalisations pour EIM chez les sujets âgés de plus de 60 ans, suggérant une incidence de 17 %. Une étude prospective au Royaume-Uni [9] en 2010 ayant pour but de déterminer le taux d'incidence de réhospitalisation pour EIM chez les 1000 premiers patients hospitalisés avait estimé ce taux à 17 ‰ patients-année. Notre taux d'incidence de 17,8 ‰ patients-année est donc comparable à notre étude antérieure au CHU de Toulouse et à celle réalisée au Royaume-Uni.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…L'étude de Zhang et al [8] avait analysé rétrospectivement les facteurs prédictifs de réhospitalisations pour EIM chez les sujets âgés de plus de 60 ans, suggérant une incidence de 17 %. Une étude prospective au Royaume-Uni [9] en 2010 ayant pour but de déterminer le taux d'incidence de réhospitalisation pour EIM chez les 1000 premiers patients hospitalisés avait estimé ce taux à 17 ‰ patients-année. Notre taux d'incidence de 17,8 ‰ patients-année est donc comparable à notre étude antérieure au CHU de Toulouse et à celle réalisée au Royaume-Uni.…”
Section: Discussionunclassified
“…En fonction de la méthodo-logie (rétrospective ou prospective), la durée de suivi, le mode de recueil ou le service concerné, les résultats sont variables. À ce jour, peu de données concernent la réhospitalisation pour EIM et les données varient selon les méthodes d'étude : 17 % dans les 3 ans suivant la première hospitalisation pour Zhang et al [8], 17 ‰ au Royaume-Uni à travers une étude prospective [9] et 4,2 % au cours d'une autre étude prospective réalisée en Allemagne [10]. Teymoorian et al suggéraient une prévalence de 24,3 % chez les sujets > 80 ans dans le mois suivant la première hospitalisation aux États-Unis [11].…”
Section: Introductionunclassified
“…2,3 Improved discharge information and patient education are core principles for reducing unintentional medication changes, patient harm and hospital re-admissions. 4,5 In the United Kingdom (UK), Medicines Use Reviews (MURs), face-to-face consultations between a patient and their regular community pharmacist, are designed to identify any problems or information needs patients have with medicines and offer solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] This includes patient nonadherence to prescribed drug therapy, which by itself leads to treatment failures and wasted resources costing $150 billion annually. 8 A recent study by Budnitz et al 7 identified the drugs involved in 88.3% of emergency hospital admissions of older adults caused by adverse drug events: hematologic, endocrine, cardiovascular, central nervous system, and anti-infective agents.…”
Section: Patients At Risk For Readmissionmentioning
confidence: 99%